2013
DOI: 10.4161/bioe.26569
|View full text |Cite
|
Sign up to set email alerts
|

Potential of aSaccharomyces cerevisiaerecombinant strain lacking ethanol and glycerol biosynthesis pathways in efficient anaerobic bioproduction

Abstract: Saccharomyces cerevisiae shows high growth activity under low pH conditions and can be used for producing acidic chemicals such as organic acids as well as fuel ethanol. However, ethanol can also be a problematic by-product in the production of chemicals except for ethanol. We have reported that a stable low-ethanol production phenotype was achieved by disrupting 6 NADHdependent alcohol dehydrogenase genes of S. cerevisiae. Moreover, the genes encoding the NADH-dependent glycerol biosynthesis enzymes were furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…In fact, most of the S. cerevisiae strains possess several ADH genes codifying for alcohol dehydrogenases (although the number might vary depending on the strain background), and it has been shown that mutating a single gene have no effect in ethanol production whatsoever. Due to compensatory mechanisms, no significant ethanol reduction is detected unless a combination of several ADH genes is knocked down at the same time (Ida et al ., ; Hirasawa et al ., ). This indicates that in order to achieve a desired amount of ethanol production, those compensatory genetic mechanisms have to be very well analysed and predicted.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, most of the S. cerevisiae strains possess several ADH genes codifying for alcohol dehydrogenases (although the number might vary depending on the strain background), and it has been shown that mutating a single gene have no effect in ethanol production whatsoever. Due to compensatory mechanisms, no significant ethanol reduction is detected unless a combination of several ADH genes is knocked down at the same time (Ida et al ., ; Hirasawa et al ., ). This indicates that in order to achieve a desired amount of ethanol production, those compensatory genetic mechanisms have to be very well analysed and predicted.…”
mentioning
confidence: 97%
“…Gpd1p/Gpd2p use glyceraldehyde-3-phosphate derived from glycolysis, and its production is regulated according to cell demands. (Ida et al, 2012;Hirasawa et al, 2014). This indicates that in order to achieve a desired amount of ethanol production, those compensatory genetic mechanisms have to be very well analysed and predicted.…”
mentioning
confidence: 99%